Improvement of anaemia in haemodialysed patients after viral or toxic hepatic cytolysis. Issue 6218 (29th March 1980) - Simon, P; Meyrier, A; Tanquerel, T; Ang, K S
Abstract : Thirty patients receiving haemodialysis, including two who had undergone bilateral nephrectomy, showed significant increases (p less than 0.001) in packed cell volume, haemoglobin concentration, and reticulocyte count during an episode of viral or toxic liver cytolysis. In 19 cases the episode lasted a mean of 5.0 +/- SD 2.9 months and was accompanied by improved haematological values for a mean of 12.0 +/- 6.0 weeks. Of the remaining patients, in whom the episode lasted a mean of 8.0 +/- 3.5 months (p less than 0.02), seven showed continued improvement a mean of 30.0 +/- 16.0 weeks after cytolysis. In eight patients in this group there was an apparent correlation between persistently increased haemoglobin concentrations and biopsy evidence of chronic hepatitis. The findings suggest that the reduction in anaemia resulted from enhanced red-cell production mediated by secretion of erythropoietin from regenerating liver cells. If confirmed this might have important implications for the treatment of anaemia in chronic renal insufficiency.